Monsieur de Camors $1 (BVolume 2s - Feuillet, Octave, 1821-1890 (Salt Lake City, UT : Project Gutenberg, 2003)
"Monsieur de Camors $1 (BVolume 2" by Octave Feuillet is a novel written in the late 19th century. The story unfolds around the character M. de Camors, who contemplates his future in politics while becoming increasingly entangled in a complex relationship with Madame de Tecle, a woman of virtue and grace. The intricacies of their interactions hint at themes of ambition, love, and social dynamics, set against a backdrop of romantic ideals and societal pressures. At the start of the narrative, we find the young Count M. de Camors visiting Madame de Tecle in her garden, where she is absorbed in her work on tapestry. Their conversation evolves from political counsel to deeper sentiments, revealing Camors' ambitions and his need for her support in his political aspirations. Throughout their dialogue, it is clear that both characters are wrestling with their emotions, as Madame de Tecle remains cautious about his intentions. The dynamic between them shifts from a straightforward friendship to a complex interplay of admiration and desire, suggesting that feelings not only linger but deepen, complicating their lives further. As Camors continues to navigate his ambitions, he finds himself genuinely drawn to Madame de Tecle, leading to both personal and political dilemmas that encapsulate the drama of the ensuing narrative. (This is an automatically generated summary.)s
Release date is 2003-04-01
This etext was produced by David Widger
Keywords: Paris (France) -- Fiction